Mental health nurses' perspectives of people who self‐harm. (12th November 2020) - McGough, Shirley; Wynaden, Dianne; Ngune, Irene; Janerka, Carrie; Hasking, Penelope; Rees, Clare
Abstract: Self‐harm is a significant health issue, a leading cause of serious injury and is an indicator of psychological distress. Nurses play an important role in providing therapeutic care to people who self‐harm. The aim of this study was to explore mental health nurses' (MHNs) experience of working with people who self‐harm. Data were collected using semi‐structured interviews and transcribed verbatim from 14 MHNs across Australia. Elo and Kyngäs' inductive content analysis was used to extract meaning from the data which is reported in accordance with the consolidated criteria for qualitative research guidelines (COREQ). Two categories were identified which captured the MHNs' experiences of working with people who self‐harm: (i) Nurses' level of preparedness to work with people who self‐harm; and (ii) The healthcare system. Several sub‐categories were identified. Attitudes, knowledge, skills, and support from others influenced their experience of working with people who self‐harm. Clinical and life experience, undergraduate programme preparation and ongoing education all contributed towards developing therapeutic care with this group of patients. Nurses are vital in the care of people who self‐harm and an accurate understanding of the functions of self‐harm focuses therapeutic interactions to manage psychological distress and reduce further self‐harm and lessen the risk of suicide.